Analisis Prioritas Platform E-Commerce Bagi Generasi Z Menggunakan Metode SAW - Agus Ariawan; Andreas Tigor Oktaga (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This study analyzes e-commerce platform preferences for digital marketing strategies among Generation Z students at the Institut Teknologi dan Bisnis Semarang using the Simple Additive Weighting (SAW) method. By evaluating four platforms (Tokopedia, Lazada, Shopee, TikTok) based on ease of use (25%), user experience (25%), promotions (15%), transaction security (15%), and product completeness (15%), the results show that Shopee leads (0.9333) with the best interface and features. TikTok (0.9080) excels in promotions but lacks security, Tokopedia (0.8820) remains consistent, while Lazada (0.8084) needs UX improvements. The implications suggest that platforms should optimize mobile interfaces, collaborate with influencers, and enhance visual search features to meet Gen Z’s demand for interactive experiences and economic value..